2010
DOI: 10.1158/1535-7163.mct-09-1036
|View full text |Cite
|
Sign up to set email alerts
|

1,25-Dihydroxyvitamin D3 Enhances the Apoptotic Activity of MDM2 Antagonist Nutlin-3a in Acute Myeloid Leukemia Cells Expressing Wild-type p53

Abstract: The tumor suppressor p53 is often referred to as "the guardian of the genome" because of its central role in the cellular response to oncogenic stress and prevention of tumor development. Mutations of p53 in acute myeloid leukemia (AML) are rare but resistance to chemotherapy has been reported because of the deregulation of the p53 signaling and differentiation pathways. It is known that the interaction of the vitamin D metabolite 1,25-dihydroxyvitamin D 3 (1,25D) with its functional vitamin D receptor leads t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…We have previously shown that 1,25D can induce differentiation of p53wt as well as p53null AML cells, 29 but the effect of the vitamin D-based "differentiation cocktail" was not previously investigated. Values are the mean ± sD (n = 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that 1,25D can induce differentiation of p53wt as well as p53null AML cells, 29 but the effect of the vitamin D-based "differentiation cocktail" was not previously investigated. Values are the mean ± sD (n = 3).…”
Section: Resultsmentioning
confidence: 99%
“…34,35 These data seem to nicely complement our recent study using wild-type p53 cells that focused on the effects of 1,25D on cell survival in relation to p53 expression. 29 We showed there that in AML cell lines with endogenous p53wt, exposure to 1,25D enhances the apoptotic activity of the MDM2 antagonist nutlin 3a, which stabilizes the protein levels of p53, and that the pro-apoptotic effect of the combination of 1,25D with nutlin3a was most likely due to the upregulation of PIG-6 and/or the downregulation of one or more of the survival proteins BCL-2, MDMX, hKSR2 or ERK1/2 activated by phosphorylation. 29 The observation noted in that study that activated ERK1/2 is downregulated by the 1,25D-nutlin 3a combination is reminiscent of the finding here that 1,25D combination with antioxidants, especially carnosic acid in combination with the p38 inhibitor also reduce the levels of activated ERK1/2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of nutlin-3a with 1,25(OH) 2 D 3 enhanced apoptosis in wild-type p53 expressing MOLM-13 and OCI-AML3 cells in vitro by suppressing anti-apoptitic protein BCL-2 and p90RSK and by inducing the pro-apoptotic protein PIG-6 [153].…”
Section: Mdm2 Antagonistmentioning
confidence: 96%
“…It was recently shown that vitamin D alone induced monocytic differentiation of two wild-type p53 AML cell lines as well as a p53-null AML cells. Combination of a small molecule inhibitor (nutlin-3a) of p53-MDM2 interaction and vitamin D accelerated programmed cell death (Thompson, Andreeff et al 2010). Interestingly, MDM2 levels dropped significantly in the presence of vitamin D 3 , possibly contributing to the apoptotic effect.…”
Section: Leukemia Vitamin D and The Effect On Tumor Suppressor Genesmentioning
confidence: 97%